An inexpensive, temporally integrated system for monitoring occurrence and biological effects of aquatic contaminants in the field. (20th May 2014) - Kahl, Michael D.; Villeneuve, Daniel L.; Stevens, Kyle; Schroeder, Anthony; Makynen, Elizabeth A.; LaLone, Carlie A.; Jensen, Kathleen M.; Hughes, Meagan; Holmen, Bruce A.; Eid, Evan; Durhan, Elizabeth J.; Cavallin, Jenna E.; et al.
Abstract Assessment of potential risks of complex contaminant mixtures in the environment requires integrated chemical and biological approaches. In support of the US Great Lakes Restoration Initiative, the US Environmental Protection Agency lab in Duluth, MN, is developing these types of methods for assessing possible risks of aquatic contaminants in near‐shore Great Lakes (USA) sites. One component involves an exposure system for caged fathead minnow (Pimephales promelas) adults suitable for the wide range of habitat and deployment situations encountered in and around the Great Lakes. To complement the fish exposure system, the authors developed an automated device for collection of composite water samples that could be simultaneously deployed with the cages and reflect a temporally integrated exposure of the animals. The present study describes methodological details of the design, construction, and deployment of a flexible yet comparatively inexpensive (<600 USD) caged‐fish/autosampler system. The utility and performance of the system were demonstrated with data collected from deployments at several Great Lakes sites. For example, over 3 field seasons, only 2 of 130 deployed cages were lost, and approximately 99% of successfully deployed adult fish were recovered after exposures of 4 d or longer. A number of molecular, biochemical, and apical endpoints were successfully measured in recovered animals, changes in which reflected known characteristics of the study sites (e.g., upregulation of hepatic genes involved in xenobiotic metabolism in fish held in the vicinity of wastewater treatment plants). The automated composite samplers proved robust with regard to successful water collection (>95% of deployed units in the latest field season), and low within‐ and among‐unit variations were found relative to programmed collection volumes. Overall, the test system has excellent potential for integrated chemical–biological monitoring of contaminants in a variety of field settings. Environ Toxicol Chem 2014;33:1584–1595. © 2014 SETAC